2015
DOI: 10.21608/ejnf.2015.104671
|View full text |Cite
|
Sign up to set email alerts
|

Effect Feeding of Supplemented Ration With Algae on Milk Yield and Its Composition for Damascus Goats

Abstract: he objective of the present investigation was to study the effect of two supplemented algae on nutritive value of lactating Damascus goats rations and its effect on performance of kids, milk production, milk composition, digestion coefficients, feed intake and feed conversion. Twenty seven Damascus lactating goats of 2-4 years old and average live body weight of 48.5±1.4kg were chosen divided and into three similar groups (9 animals each) R1 (control), R2 and R3. The groups were assigned at random to receive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…Increase the total protein of plasma maybe it is why too high protein content in Spirulina algae (Gershwin and Belay, 2008). Current results are consistent with the findings that recognized by Hassanien et al (2015) who worked with goats and used Spirulina algae at 0.2% of their feed intake. Likewise, Hafez et al (2013) found that blood total protein and albumin concentrations were significant higher with 0.2% Spirulina platens algae of DMI of growing lambs than those of control diet that free from algae supplement.…”
Section: Blood Constitutessupporting
confidence: 92%
“…Increase the total protein of plasma maybe it is why too high protein content in Spirulina algae (Gershwin and Belay, 2008). Current results are consistent with the findings that recognized by Hassanien et al (2015) who worked with goats and used Spirulina algae at 0.2% of their feed intake. Likewise, Hafez et al (2013) found that blood total protein and albumin concentrations were significant higher with 0.2% Spirulina platens algae of DMI of growing lambs than those of control diet that free from algae supplement.…”
Section: Blood Constitutessupporting
confidence: 92%